Scleroderma, Myositis and Related Syndromes 2019
DOI: 10.1136/annrheumdis-2019-eular.3185
|View full text |Cite
|
Sign up to set email alerts
|

Fri0338 anti-Mda5 Idiopathic Inflammatory Myositis (Iim) Confers Poor Prognosis but Negative Myositis Specific Antibody (Msa) Is Not Benign Either

Abstract: BackgroundMSA test is useful to diagnose IIM and subcategorize patients by disease phenotypes.ObjectivesThe study aims to evaluate the survival of IIM patients of different MSA patterns.MethodsAn IIM registry had been set up in a tertiary referral centre since 2014 by recruiting prevalent and incident cases. Patients were followed-up prospectively. This study included patients fulfilling the 2017 EULAR/ACR classification criteria for IIM1 and excluded those aged < 18 at disease onset. Immunoblot EUROLINE autoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a Japanese cohort of DM patients tested positive for anti-MDA5, 46% died within 6 months from disease onset due to respiratory failure [15]. Our local experience indicated that the one-year survival of IIM patients with the anti-MDA5 was 43% [16].…”
Section: Introductionmentioning
confidence: 82%
“…In a Japanese cohort of DM patients tested positive for anti-MDA5, 46% died within 6 months from disease onset due to respiratory failure [15]. Our local experience indicated that the one-year survival of IIM patients with the anti-MDA5 was 43% [16].…”
Section: Introductionmentioning
confidence: 82%